Design and Analysis of Biogas Register - Khaled Zaid; Ahmed Khader; Taqi-Adyn Atili; Aanas Malik (My University, 2011)
Renewable energy is a very important and useful source of energy, it is widely used in all over the world, now it is time to be applied in our regions, for the case of Palestine, the most feasible renewable energy source to be applied is the biomass source, knowing that Palestine is a green country and have wide areas of animal and plant farms, so it would be easy to change the manure of those farms into a useful biogas which can help in the independence of energy of our country. Biogas production process is not easy, it is a chemical process which needs deep studies and knowledgment of the total chemecal reactions that take place during the digestion process, and the factors that could affect this process. Biogas digester consists of several components, in simple digesters it consists of mixing bit, digester, gasholder and the inlet and outlet ways. Many other component can be provided to the system depending on the conditions and the type of digester and manure it dealing with. It is easy to make an experimental process of a biogas digester, and this small sample can give a large amount of information about the digestion process and factors surrounding it. On the other hand, making a large scale biogas register or a biogas plant needs an economic study for feasibility of the project. Applying a biogas register system to a chicken farm consist of 20,000 chicken, can give the farm back an amount of gas which can operate the heating and lighting systems by converting this gas into electricity using a cogeneration unit. This process can help the farm independent from outside supplies, it brings life to the farm! Palestine is a rich country of plants and animals, which can give a large amount of manures, which in result can be the fuel of biogas digesters that can provide the Palestinian farms the needed energy for its various operations. This project was dedicated to apply a practical experiment of using chicken biomass to produce biogas, using a sample of small scale digester build from simple parts, and check whether it really produces a biogas or not, taking all readings of biogas weight. As a result biogas was obtained day after day and reached its maximum production on the 39th day approximately. It was realized that the total biogas production for nine kilogram of chicken biomass equals to 0.830 Kg , theoretically, it is known that nine kilograms of chicken biomass gives 1.044 Kg of biogas, which leads to an error of 20.49%. Small scale experiment was taken into further implementation on a chicken farm containing 20,000 head of chicken. A whole system of biomass collector, mixer, digester and gasholder. Total loads of heating and lighting for the farm was calculated and that leaded to a production that covered the needed demand. Payback point was analyzed and it was found that initial cost of the system would be returned in a reasonable period.